Muscular Activation Pattern of Bilateral Extensors Response to Asymmetric Hand Lifting During Trunk Flexion–extension Performance. Issue 4 (4th July 2017) - Wei, Ying; Shan, Xinhai
ABSTRACT: The authors' purpose was to test the effect of asymmetric hand lifting on muscular activation patterns of 3 bilateral extensors. Eighteen male university students without back pain were volunteered. Each performed flexion–extension randomly with conditions of right lifting, left lifting, and nonlifting. Surface electromyography from bilateral thoracic, lumbar erector spinae, and hamstring was recorded. The cross-correlation and relative intensity in paired muscles of bilateral extensors was calculated in flexion as well as extension period. The results showed that the cross-correlation coefficient was decreased and the phase lag as well as the relative intensity of bilateral extensors was increased significantly in thoracic level. The phase lag as well as the relative intensity of bilateral extensors was increased significantly in lumbar level. It was concluded that asymmetric lifting has a significant effect on muscular activation of bilateral extensors in thorax level, which causes the ipsilateral extensor to activate larger and longer. Asymmetric lifting also has some effect on muscular activation of bilateral extensors in lumbar level but with less extent than in thorax level, which causes contralateral extensor to activate larger and longer. Asymmetric lifting seems to have no significant effect on muscular activation of bilateral hamstring.